Proceedings of the Twenty-Fourth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973105.50
|View full text |Cite
|
Sign up to set email alerts
|

Playing Mastermind with Many Colors

Abstract: We analyze the general version of the classic guessing game Mastermind with n positions and k colors. Since the case k ≤ n 1−ε , ε > 0 a constant, is well understood, we concentrate on larger numbers of colors. For the most prominent case k = n, our results imply that Codebreaker can find the secret code with O(n log log n) guesses. This bound is valid also when only black answer-pegs are used. It improves the O(n log n) bound first proven by Chvátal (Combinatorica 3 (1983), [325][326][327][328][329]. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…It starts with the questions (0, 1), (2, 3), (4,5), i.e., we use questions of the pattern (2i, 2i + 1). At most two of them can receive a non-empty answer.…”
Section: Algorithm For Two Pegsmentioning
confidence: 99%
See 3 more Smart Citations
“…It starts with the questions (0, 1), (2, 3), (4,5), i.e., we use questions of the pattern (2i, 2i + 1). At most two of them can receive a non-empty answer.…”
Section: Algorithm For Two Pegsmentioning
confidence: 99%
“…Furthermore, we obtained additional values f (p, c) by a computer search. Recently, Doerr et al have shown that f (c, c) = O(c log log c) [4], improving the classical result f (c, c) = O(c log c) of Chvátal [3]. Also many variants of Mastermind have been investigated in the literature.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…We could stop at that and call MasterMind a worthwhile challenge, but it so happens that solving MasterMind can also be used to break ATMs guessing PINs [6] and even for an operation in biotechnology called selective phenotyping [7]. Not only that, but since it is a problem which is NP-Hard [8] the issue of finding bounds to the number of guesses needed is still open [9]. Therefore, there is room for making new venues into finding better or faster solutions to the game of MasterMind such as the heuristic solution we present in this paper.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%